2006
DOI: 10.2151/sola.2006-037
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of Optical Thickness and Effective Particle Radius of Thin Low-Level Water Clouds using the Split Window of Meteosat-8

Abstract: We developed a method to retrieve the optical thickness ( ) and effective particle radius (re) of water clouds using the split-window channels and the 8.7-µm channel of Meteosat-8. Valid ranges are approximately from 1 to 9 for and smaller than 18 µm for re. Water clouds were first identified using 8.7-µm and 11-µm data. The retrieval used the brightness temperature (TBB) and brightness temperature difference (BTD) between the split windows, as computed with the radiation code RSTAR5b for various properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Inoue et al reported BTD vs. T11 scatter charts of ice cloud [9], [14] and of water cloud [9], [15] . BTD is the abbreviation of Brightness Temperature Difference (BTD=T11-T12=-AVI).…”
Section: Property Of Avi In the Case Of Cloudmentioning
confidence: 99%
“…Inoue et al reported BTD vs. T11 scatter charts of ice cloud [9], [14] and of water cloud [9], [15] . BTD is the abbreviation of Brightness Temperature Difference (BTD=T11-T12=-AVI).…”
Section: Property Of Avi In the Case Of Cloudmentioning
confidence: 99%